Relationship between Knowledge Level and Preventive Behavior of SepticArthritis in Student Batch 2019-2020, Faculty of Medicine, University of NorthSumatra - Christine Silalahi (Indonesian Journal of Rheumatology, 2024)
Background: Septic arthritis is an infectious disease that severely damagesthe joints with clinical manifestations such as swelling, erythema andwarmth of the affected joint. The most common cause of this disease is theresult of hematogenous spread of microorganisms. Some of the risk factorsinclude injection drug use, prosthetic joints and skin infection. The incidenceof septic arthritis is 5 to 8 per 100,000 population per year with 5-10%mortality rate, therefore preventive behavior is needed to minimize theincidence of septic arthritis. Methods: This study is an observationalanalytic study with a cross-sectional approach. The research populationconsisted of students from batch 2019-2020 of the Faculty of Medicine,University of North Sumatra and the sample was determined using stratifiedrandom sampling method. Primary data were obtained directly from researchsubjects using questionnaires via Google Forms. Results: The univariateresearch analysis found that the knowledge level of the majority ofrespondents was in the good category, with 45 subjects (53.6%). The mostpredominant behavior observed in the respondents was negative behavior,with 49 subjects (58.3%). Bivariate analysis found that there was nosignificant relationship between knowledge level and septic arthritisprevention behavior with p value = 0.809. Conclusion: Students from batch2019-2020 of the Faculty of Medicine, University of North Sumatra, onaverage have a good level of knowledge and negative behavior on theprevention of septic arthritis. There is no relationship between the level ofknowledge with septic arthritis prevention behavior.